2015
DOI: 10.1016/s2213-8587(15)00225-9
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function in critically ill patients

Abstract: Patients in the intensive care unit (ICU) typically present with decreased concentrations of plasma tri-iodothyronine, low thyroxine, and normal range or slightly decreased concentration of thyroid-stimulating hormone. This ensemble of changes is collectively known as non-thyroidal illness syndrome (NTIS). The extent of NTIS is associated with prognosis, but no proof exists for causality of this association. Initially, NTIS is a consequence of the acute phase response to systemic illness and macronutrient rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
331
4
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(345 citation statements)
references
References 92 publications
4
331
4
6
Order By: Relevance
“…This condition, known as nonthyroidal illness, is typically characterized by normal serum TSH levels combined with low serum triiodothyronine and FT4 levels. 35 In contrast, we found an association of higher rather than lower FT4 levels with an increased risk of atherosclerotic manifestations. Additionally, nonthyroidal illness occurs mainly in critically ill patients, whereas our population consists of relatively healthy community-dwelling adults.…”
Section: Discussioncontrasting
confidence: 74%
“…This condition, known as nonthyroidal illness, is typically characterized by normal serum TSH levels combined with low serum triiodothyronine and FT4 levels. 35 In contrast, we found an association of higher rather than lower FT4 levels with an increased risk of atherosclerotic manifestations. Additionally, nonthyroidal illness occurs mainly in critically ill patients, whereas our population consists of relatively healthy community-dwelling adults.…”
Section: Discussioncontrasting
confidence: 74%
“…In the Netherlands, CH screening is primarily based on thyroxine (T4) screening with supplementary thyrotropin (TSH) and thyroxine-binding globulin measurements aimed at identifying not only children with primary hypothyroidism but also children with central hypothyroidism [2]. However, interpretation of the screening results can be complicated by factors that can transiently reduce thyroid hormone concentrations, such as prematurity [3], drug use [4], cardiac surgery [5], and critical illness [6]. This condition of disturbed thyroid hormone concentrations (low T4 and low triiodothyronine, increased reverse triiodothyronine, and normal or low TSH) during critical illness is referred to as nonthyroidal illness syndrome (NTIS) or euthyroid sick syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…This condition of disturbed thyroid hormone concentrations (low T4 and low triiodothyronine, increased reverse triiodothyronine, and normal or low TSH) during critical illness is referred to as nonthyroidal illness syndrome (NTIS) or euthyroid sick syndrome. It is important to distinguish between CH and NTIS because CH therapy should be initiated as soon as possible, whereas treatment for NTIS is not recommended [6]. In previous studies critically ill neonates have had lower thyroid hormone concentrations than healthy neonates [7,8,9], and this has been associated with a prolonged hospital stay and a higher mortality [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Poor outcomes may result from this aggravating of the disease condition. 26 A Dutch study showed that low thyroid hormone in critically ill patients can cause death. 27 Also, a study in Turkey reported that the levels of T3, T4, FT3 and FT4 were lower in children with septic shock, compared to sepsis-related mortality of patients with sepsis.…”
Section: Resultsmentioning
confidence: 99%